2003
DOI: 10.1177/107110070302400213
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Plantar Fascia Release: A Case Series

Abstract: Plantar fasciitis is a common disabling condition that can be recalcitrant to treatment. Endoscopic Plantar Fascia Release (EPFR) has received greater attention in recent years as a viable, and possibly superior, alternative to established open procedures for the treatment of plantar fasciitis. In a series of 17 patients (17 feet) with follow-up over an average of 16 months, we report a two portal endoscopic technique of partial release of the plantar fascia, as a successful, safe and reliable procedure for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
1
36
1
Order By: Relevance
“…A reasonable improvement of symptoms was achieved at 3 months, and progressive improvement occurred until the 1 year follow-up. This is comparable with the results reported by many studies [4,5,11,26].…”
Section: Discussionsupporting
confidence: 92%
“…A reasonable improvement of symptoms was achieved at 3 months, and progressive improvement occurred until the 1 year follow-up. This is comparable with the results reported by many studies [4,5,11,26].…”
Section: Discussionsupporting
confidence: 92%
“…When compared anecdotally to the traditional open procedure, the endoscopic approach gives superior results in these important outcome measures, similar to those reported by others. In a smaller case series report involving 17 patients who underwent uniport endoscopic release, Boyle and Slater (8) reported that 82.4% of subjects had mild to no pain postoperatively. Similarly, Brekke and Green (7) reported a mean reduction in pain of 71.5% with a dualportal endoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no consensus has been reached on which of the various endoscopic approaches is best (1). Investigators have described uni-and multiport procedures both with and without insufflations (8)(9)(10). Beginning in 2001, the principal investigator (T.N.M.)…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] The technique has been modified to remove the plantar calcaneal spur 18 and plantar calcaneal bursa. 19 However, the deep abductor hallucis fascia cannot be released by the reported techniques of endoscopic plantar fascia release.…”
Section: Discussionmentioning
confidence: 99%